2022
DOI: 10.3390/molecules27248709
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Potential of Commonly Available Fruit Plants in Bangladesh: Updates on Prospective Phytochemicals and Their Reported MoAs

Abstract: Diabetes mellitus is a life-threatening disorder affecting people of all ages and adversely disrupts their daily functions. Despite the availability of numerous synthetic-antidiabetic medications and insulin, the demand for the development of novel antidiabetic medications is increasing due to the adverse effects and growth of resistance to commercial drugs in the long-term usage. Hence, antidiabetic phytochemicals isolated from fruit plants can be a very nifty option to develop life-saving novel antidiabetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 242 publications
0
6
0
Order By: Relevance
“…Diabetes mellitus (DM) is a complex condition defined by elevated blood sugar levels brought on by deficiencies in insulin secretion and/or action. Diabetes is typically treated by altering either the lipid or glucose metabolism, or both [ 62 , 63 ]. Developing diabetes complications is a global health issue that millions of people must deal with.…”
Section: Resultsmentioning
confidence: 99%
“…Diabetes mellitus (DM) is a complex condition defined by elevated blood sugar levels brought on by deficiencies in insulin secretion and/or action. Diabetes is typically treated by altering either the lipid or glucose metabolism, or both [ 62 , 63 ]. Developing diabetes complications is a global health issue that millions of people must deal with.…”
Section: Resultsmentioning
confidence: 99%
“…The primary causes of high blood sugar in individuals with diabetes are reduced insulin secretion by the beta-cells in the pancreas and reduced insulin sensitivity in the liver and muscle cells. Chronic hyperglycemia in diabetics results in micro- and macrovascular consequences, including cardiovascular disorders, diabetic retinopathy, neuropathy, and nephropathy [ 3 , 5 ]. L. glutinosa is a traditional herbal remedy that is frequently used to treat diarrhea and dysentery [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [ 5 ] reported that 4΄- O -methyl (2″,4″-di- E -p-coumaroyl) afzelin (compound 1) and its three more analogues exerted IC 50 values 5.9 to 35.3 μM, which is 8 to 91 times more potent than the standard drug acarbose (IC 50 = 266.1 μM) against the α-glucosidase enzyme, which is associated with carbohydrate digestion in small intestine. Thus, the flavonoid glycosides prevent carbohydrates from being cleaved, reducing glucose absorption and lowering postprandial glycemic levels [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medicinal plants account for 10% of all vascular plants (Fonnegra and Jiménez, 2007), comprising almost half a million species (Pimm et al, 2014). When no synthetic medications were available and no idea of surgery existed, the plant kingdom aided greatly in the treatment of ailments (Akinyemi et al, 2018;Alam et al, 2022). The usage of these plants has been developed over the generations and this has become known in many contexts as traditional medicine.…”
Section: Introductionmentioning
confidence: 99%